Boosting Employee Engagement And Collaboration - Nugraha, Andika Prasetya; Suriani, Suci (Program Pascasarjana STIE Amkop Makassar, 2023)
Research at the Regional Public Works Organisation of the Regional Government of Karimun Regency is being conducted with the aim of gaining a better understanding of the effects of workplace communication and conditions on employee performance. This research is a quantitative study with statistical analysis using the multiple linear regression approach. It includes a validity test, a reliability test, and the usual assumption test. Using the IBM SPSS Statistics 26 software, the research obtained partial calculation results (t-test) for the work environment variable (X1) with a value of 5,265 and a significance level of 0.000, and for the communication variable with a value of 6,209 and a significance level of 0.000. The researcher found a value of 315,233 with a 95% degree of confidence using the results of the simultaneous test (Test F). This research found that, first, the workplace does have an effect on employee performance, and second, communication does as well, but to a lesser extent. The Public Works OPD of the Karimun Regency Regional Government wants the communication variable (X2) and the work environment variable (X1) to have a substantial impact on the staff performance variables (Y). Key Word: Work Environment, Communication, Employee Performance